2021
DOI: 10.1093/mnras/stab1198
|View full text |Cite
|
Sign up to set email alerts
|

N-body simulations of dark matter with frequent self-interactions

Abstract: Self-interacting Dark Matter (SIDM) models have the potential to solve the small-scale problems that arise in the Cold Dark Matter paradigm. Simulations are a powerful tool for studying SIDM in the context of astrophysics, but it is numerically challenging to study differential cross-sections that favour small-angle scattering (as in light-mediator models). Here we present a novel approach to model frequent scattering based on an effective drag force, which we have implemented into the N-body code Gadget-3. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 69 publications
(73 reference statements)
3
36
1
Order By: Relevance
“…Kim et al (2017) have performed a parameter study of equal-mass mergers that demonstrated that offsets between DM and galaxies can arise from rare self-interactions. Building on this, Fischer et al (2021) showed that even larger offsets arise when fSIDM is considered, as expected by Kahlhoefer et al (2014). Unequal-mass mergers are interesting since they occur much more frequently than equal-mass mergers.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Kim et al (2017) have performed a parameter study of equal-mass mergers that demonstrated that offsets between DM and galaxies can arise from rare self-interactions. Building on this, Fischer et al (2021) showed that even larger offsets arise when fSIDM is considered, as expected by Kahlhoefer et al (2014). Unequal-mass mergers are interesting since they occur much more frequently than equal-mass mergers.…”
Section: Introductionmentioning
confidence: 63%
“…For our simulations we use the cosmological 𝑁-body code -3, which is a successor of -2 . For rare and frequent self-interactions we are using the implementation described in Fischer et al (2021). This means that for the rare self-interactions a similar scheme to the one introduced by Rocha et al ( 2013) is used and the scheme for frequent self-interactions is based on an effective description employing a drag force (Kahlhoefer et al 2014) and was introduced in Fischer et al (2021).…”
Section: Simulation Code and Implementation Of Self-interactionsmentioning
confidence: 99%
See 3 more Smart Citations